2021
DOI: 10.1080/22423982.2021.1966924
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of socially significant infectious diseases (HIV, TB and HIV/TB coinfection) in the Arctic regions of Russia)

Abstract: The study is aimed to evaluate the HIV, TB, and HIV/TB coinfection incidence per 100,000 population/year in Russian Arctic, based on official statistical data. The epidemics’ incidence in Russian Arctic is uneven. The highest HIV incidence in 2019 was registered in Krasnoyarsk region (94,6), and the highest TB incidence in ChAD (136,1). ChAD was also identified as the region with the worst indicators, where the HIV incidence in 2007–2019 was evaluated at (315,8%), TB (136,1%), HIV/TB coinfection (150,0%). Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The findings of this study demonstrated a significant and consistent decrease in the number of new HIV infection cases in Russia from 2015 to the present, aligning with previous research findings [23,24]. Additionally, a notable increase in the coverage of HIV testing was observed throughout the observation period (2011-2022).…”
Section: Discussionsupporting
confidence: 90%
“…The findings of this study demonstrated a significant and consistent decrease in the number of new HIV infection cases in Russia from 2015 to the present, aligning with previous research findings [23,24]. Additionally, a notable increase in the coverage of HIV testing was observed throughout the observation period (2011-2022).…”
Section: Discussionsupporting
confidence: 90%
“…Studies performed to date mainly focused on regions and cities in which the HIV epidemic has been particularly acute, including Kemerovo, Sverdlovsk, St. Petersburg, and Krasnoyarsk [5][6][7]. Although the problems associated with HIV infection have received some attention at the national level, there is only limited knowledge of its impact from a sub-national (oblast) perspective.…”
Section: Introductionmentioning
confidence: 99%